Evaluating the effects of pH, hardness, and dissolved organic carbon on the toxicity of aluminum to freshwater aquatic organisms under circumneutral conditions. (28th December 2017) - Gensemer, Robert W.; Gondek, John C.; Rodriquez, Patricio H.; Arbildua, Jose J.; Stubblefield, William A.; Cardwell, Allison S.; Santore, Robert C.; Ryan, Adam C.; Adams, William J.; Nordheim, Eirik
Abstract: Although it is well known that increasing water hardness and dissolved organic carbon (DOC) concentrations mitigate the toxicity of aluminum (Al) to freshwater organisms in acidic water (i.e., pH < 6), these effects are less well characterized in natural waters at circumneutral pHs for which most aquatic life regulatory protection criteria apply (i.e., pH 6–8). The evaluation of Al toxicity under varying pH conditions may also be confounded by the presence of Al hydroxides and freshly precipitated Al in newly prepared test solutions. Aging and filtration of test solutions were found to greatly reduce toxicity, suggesting that toxicity from transient forms of Al could be minimized and that precipitated Al hydroxides contribute significantly to Al toxicity under circumneutral conditions, rather than dissolved or monomeric forms. Increasing pH, hardness, and DOC were found to have a protective effect against Al toxicity for fish ( Pimephales promelas ) and invertebrates ( Ceriodaphnia dubia, Daphnia magna) . For algae ( Pseudokirchneriella subcapitata), the protective effects of increased hardness were only apparent at pH 6, less so at pH 7, and at pH 8, increased hardness appeared to increase the sensitivity of algae to Al. The results support the need for water quality–based aquatic life protection criteria for Al, rather than fixed value criteria, as being a more accurate predictor of Al toxicity in natural waters. Environ Toxicol Chem 2018;37:49–60. © 2017 SETAC